2017
DOI: 10.4014/jmb.1610.10046
|View full text |Cite
|
Sign up to set email alerts
|

Role of eptC in Biofilm Formation by Campylobacter jejuni NCTC11168 on Polystyrene and Glass Surfaces

Abstract: The complex roles of cell surface modification in the biofilm formation of Campylobacter jejuni, a major cause of worldwide foodborne diarrheal disease, are poorly understood. In a screen of mutants from random transposon mutagenesis, an insertional mutation in the eptC gene (cj0256) resulted in a significant decrease in C. jejuni NCTC11168 biofilm formation (<20%) on major food contact surfaces, such as polystyrene and borosilicate glass, when compared with wild-type cells (p < 0.05). In C. jejuni strain 81-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…To explore the relationship between DOC and an eptC mutation, an eptC deletion mutant (ΔeptC) was generated and the mutant was complemented with a copy of the wild-type gene or a copy of the gene containing the P360Q mutation. The C. jejuni wild-type strain and EptC variants were tested for Others have reported that a C. jejuni ΔeptC has reduced motility and increased polymyxin B sensitivity compared to a wild-type isolate (Scott et al, 2012;Fage et al, 2014;Lim and Kim, 2017). Motility assays revealed that the ΔeptC mutant was impaired in motility when compared to the wild-type strain, which is in agreement with previous reports (Cullen et al, 2012;Scott et al, 2012;Fage et al, 2014).…”
Section: Iib Phenotypic Characterization Of a C Jejuni Eptc Mutantsupporting
confidence: 84%
“…To explore the relationship between DOC and an eptC mutation, an eptC deletion mutant (ΔeptC) was generated and the mutant was complemented with a copy of the wild-type gene or a copy of the gene containing the P360Q mutation. The C. jejuni wild-type strain and EptC variants were tested for Others have reported that a C. jejuni ΔeptC has reduced motility and increased polymyxin B sensitivity compared to a wild-type isolate (Scott et al, 2012;Fage et al, 2014;Lim and Kim, 2017). Motility assays revealed that the ΔeptC mutant was impaired in motility when compared to the wild-type strain, which is in agreement with previous reports (Cullen et al, 2012;Scott et al, 2012;Fage et al, 2014).…”
Section: Iib Phenotypic Characterization Of a C Jejuni Eptc Mutantsupporting
confidence: 84%
“…SEM was performed as previously described 79 . The samples were fixed with Karnovsky’s glutaraldehyde (0.05 M sodium cacodylate buffer (EMS, Hatfield, PA, USA), 2% paraformaldehyde (EMS), and 2% glutaraldehyde (EMS)) at 4 °C for 2 h. After washing with 0.05 M sodium cacodylate buffer twice, the samples were incubated in 1% osmium tetroxide (EMS) with 0.05 M cacodylate buffer at 4 °C for 2 h. Then, the samples were washed in DW and dehydrated in increasing alcohol concentrations (30%, 50%, 70%, 80%, 90% and 100%).…”
Section: Methodsmentioning
confidence: 99%
“…QS is a regulatory process that allows a bacterial population to collectively express various virulence factors associated with pathogenesis including biofilm formation [ 47 - 50 ]. Targeting the QS circuits of bacteria has been found to be a promising strategy to combat bacterial infections as an alternative to conventional antibiotics [ 51 ].…”
Section: Discussionmentioning
confidence: 99%